Hair Coil Penile Tourniquet Syndrome in an Unusual Age - Kursad Zengin; Mustafa Yasar Ozdamar; Sebahattin Albayrak; Serhat Tanik; Muhittin Atar; Hasan Bakirtas; Muhammed Abdurrahim Imamoglu; Mesut Gurdal (Case Reports in Urology)
Penile tourniquet syndrome (PTS), a rare urologic emergency, may lead to undesirable results including necrosis and amputation of penis, if not diagnosed and treated appropriately. Sometimes these injuries may be accepted as a forensic case. Miscellaneous objects used for strangulation can be metallic or nonmetallic. Of all ages, the most vulnerable period is infancy. Telogen effluvium is the most common cause of PTS in infants who are 0–6 years old. In the literature, telogen effluvium as a reason of PTS was not found except for this age group. Therefore, we aimed to present a boy who is 8 years old diagnosed as PTS because of his mother’s hair coil.